Perceptions of interior design business owners challenges and strategies for establishing and managing a business - Roa, Christine Anne O. (College of Home Economics, University of the Philippines Diliman, 2023)
The interior design industry is experiencing remarkable growth in recent years, with more professionals and businesses seeking to provide design services. However, success in this field requires a good grasp of effective business practices and strategies. This thesis employed a qualitative research design with a phenomenological approach to explore the challenges and strategies employed by 10 interior design professionals from the Philippines in establishing and managing their businesses. Using purposive sampling and conducting semi-structured interviews, data was gathered and thematically analyzed. Findings revealed the interior design-related challenges were client acquisition, issues with suppliers and contractors, issues with clients, sporadic inflow of projects, overflow of clients and projects, issues with workers, and project workflow. The non-interior design-related challenges include legal requirements, starting capital, time management, business knowledge gaps, handling manpower, business sustainability, limited time, setting boundaries, people relations, managing taxes, and pricing. The effective strategies that can be employed are delegating work, continuous learning and adaptability, emotional resilience, mentorship, relationship building, client understanding and education, effective marketing, self-discovery and valuing oneself, contract enhancement, and project scheduling. The knowledge and skills that interior design students should have are personal foundations, business knowledge, psychology, interpersonal skills, and knowledge of related disciplines. The variation in perceptions may be attributed to the type of business structure employed or the different backgrounds and experiences of the respondents. These findings contribute practical insights to support the growth and sustainability of interior design businesses in the Philippines.